Evaluation of a short training course of chest X-ray interpretation for the diagnosis of paediatric TB - B. F. Melingui; E. Leroy-Terquem; M. Palmer; J-V. Taguebue; A. P. Wachinou; J. Gaudelus; A. Salomao; D. Bunnet; T. C. Eap; L. Borand; C. Chabala; C. Khosa; et al. (IJTLD Open)
BACKGROUND: Chest X-ray (CXR) interpretation is challenging for the diagnosis of paediatric TB. We assessed the performance of a three half-day CXR training module for healthcare workers (HCWs) at low healthcare levels in six high TB incidence countries. METHODS: Within the TB-Speed Decentralization Study, we developed a three half-day training course to identify normal CXR, CXR of good quality and identify six TB-suggestive features. We performed a pre–post training assessment on a pre-defined set of 20 CXR readings. We compared the proportion of correctly interpreted CXRs and the median reading score before and after the training using the McNemar test and a linear mixed model. RESULTS: Of 191 HCWs, 43 (23%) were physicians, 103 (54%) nurses, 18 (9.4%) radiology technicians and 12 (6.3%) other professionals. Of 2,840 CXRs with both assessment, respectively 1,843 (64.9%) and 2,277 (80.2%) were correctly interpreted during pre-training and post-training (P < 0.001). The median reading score improved significantly from 13/20 to 16/20 after the training, after adjusting by country, facility and profession (adjusted β = 3.31, 95% CI 2.44–4.47). CONCLUSION: Despite some limitations of the course assessment that did not include abnormal non-TB suggestive CXR, study findings suggest that a short CXR training course could improve HCWs’ interpretation skills in diagnosing paediatric TB.